Risiko Usahatani Cabai Rawit Pada Masa Tanam I dan Masa Tanam II Di Kecamatan Ranowulu Kota Bitung - Maytti Potolau; Joachim N.K. Dumais; Hanny Anapu; Juliana R. Mandei (Universitas Sam Ratulangi, 2013)
AbstractThe objective of this research are to compute anda compare the chili farming in the both first planting period and second planting period, to compute chili farming income both the first planting period and second planting period. The research location is taken intentionally (purposive sampling) of three villages as the center of the village production chili in three villages namenly Danowudu, Apela II and Kumorsot in five months, from December 2012 until May 2013. Sampling technique census is conducted on 24 respondents divided into two groups based on the first planting period and second planting period. Data used in this research is farmer’s income. Data analysis uses standard deviation, coefficient of variation and lower income limit.The results showed the risk of chili farming in the first period of planting was Rp.2.343.347 with relative level 0.41 and a lower limit of income was Rp 1.081.287. Even the risk of chili farming in the second period of planting was Rp. 4.144.513 with relative level 0.41 and a lower limit of income was Rp – 192.776. The second period of planting had greater risk than the first period of planting. The sources of risk that the chili farming experienced in first and second period of planting are the source of physical risk and the source of economic risk. That chili farming average income in the first period of planting was Rp. 5.917.732 per hectare with the range from Rp 2.854.792 per hectare to Rp 8.910.122 per hectare, and that chili farming average income in the second period of planting was Rp 8.265.574 per hectare with the range from Rp 2.577.415 per hectare to Rp 14.712.370 per hectare.Farmers need to take a risk to get more profit and to intensify their farming. Role of the government is to introduce more technology that can help the farmers in developing chili farming to make it better.